2013
DOI: 10.5897/ajpp11.742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Juniperus phoenicea extract on uricemia and activity of antioxidant enzymes in liver, erythrocyte and testis of hyperuricemic (oxonate-treated) rats

Abstract: The aim of the present study was to determine whether administration of Juniperus phoenicea extract would have any advantage over allopurinol therapy on (1) lipids peroxidation level and (2) antioxidant activity in liver, erythrocyte and testis of hyperuricemic rats by oxonate administration. In hyperuricemic rats, levels of lipids peroxidation in liver, erythrocyte and testis were found to be significantly increased as compared to control rats (p < 0.05). Activities of glutathione peroxidase (GPX), superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Many herbal plant species were explored to be antigout and reduce uric acid in blood such as Lagerstroemia speciosa [4] , Apium graveolens , Ficus carica , Curcuma domestica , C innamomum zeylanicum and Rosmarinus officinalis [79] , Erythrina strica [80] , Rhuscoriaria [81] , Juniperus phoenicea [82] , Momordica charantia , Apium gravelens , Petroselium crispum , Linum usitatissmun , Cucurbita pepo , Zingiber officinale , Curcurma longa , Cinnamomum sp., Rosmarinus sp. [56] , [83] , Origanum majorana [84] , Prunus cerasus [85] , Phyllanthus niruri [86] , Glycine max and Arabidopsis thaliana [87] , Vinca sp.…”
Section: Inhibition Of Uric Acid Synthesis By Some Plant Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many herbal plant species were explored to be antigout and reduce uric acid in blood such as Lagerstroemia speciosa [4] , Apium graveolens , Ficus carica , Curcuma domestica , C innamomum zeylanicum and Rosmarinus officinalis [79] , Erythrina strica [80] , Rhuscoriaria [81] , Juniperus phoenicea [82] , Momordica charantia , Apium gravelens , Petroselium crispum , Linum usitatissmun , Cucurbita pepo , Zingiber officinale , Curcurma longa , Cinnamomum sp., Rosmarinus sp. [56] , [83] , Origanum majorana [84] , Prunus cerasus [85] , Phyllanthus niruri [86] , Glycine max and Arabidopsis thaliana [87] , Vinca sp.…”
Section: Inhibition Of Uric Acid Synthesis By Some Plant Metabolitesmentioning
confidence: 99%
“… Lythraceae Leaves Valoneic acid dilactone (VAD) Ellagic acid (EA) [4] Apium graveolens (Celery) Umbelliferae Fresh leaves and seeds Oleic and Linoleic acid in Celery All rich in phenolics Unsaturated fatty acids, long chain fatty acids, phytosterols and Malondialdehyde Antigout, antimicrobial, Anti-inflammatory and antioxidant effects [79] Ficus carica (Fig) Moraceae Dry Fig. fruits Curcuma domestica L. (Turmeric) Zingiberaceae Rhizomes Cinnamomum zeylanicum (Cinnamon) Lauraceae Bark Rosmarinus officinalis (Rosemary) Labiatae Leaves Erythrina strica roxb Papilionaceae Hydromethanolic extract of leaves Flavonoids, saponins, tannins, phenolics and triterpenoids Inhibit xanthine oxidase (XO) and xanthine dehydrogenase (XDH) activities [80] Rhuscoriaria (sumac or sumak) Anacardiaceae Hydroalcoholic extract of fruits Phenolic (as gallic acid), methyl gallate and protocatechuic acid – Inhibit xanthine oxidase (XO) activity – Decrease Hyperuricemia [81] Juniperus phoenicea Cupressaceae Decoction of fresh leaves in water Phenols Reduce uric acid level and have antioxidant activity [82] Momordica charantia (Bitter) Cucurbitaceae Methanol-water extract of pulp Phenols and Flavonoids Inhibit xanthine oxidase [58] , [83] Apium gravelens (Celery) Umbelliferae Dried powdered leaves Petroselium crispum Umbelliferae Parsly leaves Linum usitatissmum (Flax) Linaceae Seed Cucurbita pepo (Pumpkin) ...…”
Section: Inhibition Of Uric Acid Synthesis By Some Plant Metabolitesmentioning
confidence: 99%
“…Ahmed et al (2000) found that ginger significantly lowered lipid peroxidation by maintaining the activities of antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase in blood of rats. Effects of Juniperus phoenicea extract on the activity of antioxidant enzymes in liver of oxonate-treated rats have been studied (Gdoura et al, 2013). Also, the antioxidant effects of whole ginger against lead acetate-induced liver apoptosis in rats have been studied (Khaki and Khaki, 2010).…”
Section: Introductonmentioning
confidence: 99%